ChemInform Abstract: 5, 6, 7, 8‐Tetrahydropyrido[4, 3‐c]pyridazine: A Lead‐Oriented Scaffold with Two Diversity Points. Issue 5 (4th February 2014) - Borisov, Alexander V.; Voloshchuk, Volodymyr V.; Nechayev, Maxim A.; Grygorenko, Oleksandr O.
Abstract The five step sequence for the synthesis of the title compounds includes the reaction of 4‐piperidone derivative (I) with glyoxylic acid and hydrazine as the key step.